2015
DOI: 10.5115/acb.2015.48.2.95
|View full text |Cite
|
Sign up to set email alerts
|

A single fraction fromUncaria sinensisexerts neuroprotective effects against glutamate-induced neurotoxicity in primary cultured cortical neurons

Abstract: We identified a neuroprotective single fraction among 62 ones of hexane extract from Uncaria sinensis (JGH43IA) and investigated its effects and mechanisms in primary cortical neurons. Pretreatment with JGH43IA showed a significantly increase cell viability in a dose-dependent manner with a decrease in the lactate dehydrogenase release. When we performed morphological assay and flow cytometry to determination of the type of cell death, pretreatment with JGH43IA showed a significant reduction of glutamate-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Cortical neurons were maintained in culture and excitotoxicity experiments were performed on the 9 th day of culture (DIV9). Previous studies demonstrated that neurons at DIV9 are appropriate to study glutamate toxicity as the cells are mature enough in terms of receptor expression and glutamate sensitivity [68][69][70][71]. An in vitro excitotoxicity model was established by treating cortical neurons with 100 µM glutamate for 1 hour followed by analysis at 24 hours post treatment.…”
Section: Establishment Of Glutamate Toxicity Model In Rat Primary Cormentioning
confidence: 99%
“…Cortical neurons were maintained in culture and excitotoxicity experiments were performed on the 9 th day of culture (DIV9). Previous studies demonstrated that neurons at DIV9 are appropriate to study glutamate toxicity as the cells are mature enough in terms of receptor expression and glutamate sensitivity [68][69][70][71]. An in vitro excitotoxicity model was established by treating cortical neurons with 100 µM glutamate for 1 hour followed by analysis at 24 hours post treatment.…”
Section: Establishment Of Glutamate Toxicity Model In Rat Primary Cormentioning
confidence: 99%
“…Cortical neurons were maintained in culture and excitotoxicity experiments were performed on the 9th day of culture (DIV9). Previous studies demonstrated that neurons at DIV9 are appropriate to study glutamate toxicity as the cells are mature enough in terms of NMDA receptor expression and glutamate sensitivity [86] , [87] , [88] , [89] , [90] . An in vitro excitotoxicity model was established by treating cortical neurons with 100 µM glutamate for 1 h followed by analysis at 24 h post treatment.…”
Section: Resultsmentioning
confidence: 99%